2016
DOI: 10.1097/mpg.0000000000000948
|View full text |Cite
|
Sign up to set email alerts
|

Normal Growth and Essential Fatty Acid Status in Children With Intestinal Failure on Lipid Limitation

Abstract: In this case series, lipid limitation allowed normal growth while preventing the development of cholestasis and EFA deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…In this case, we prioritized the potential to salvage the patient's native liver by reversing IFALD and avoiding the need for liver replacement over the development of EFAD with the anticipation that the latter would be short term until the patient receives a transplant and resumes the ability for oral feeding. A recent limited report from Lam et al 8 noted that at an average lipid dose of 0.69 g/kg/d of fat in a cohort of 9 children on PN, there was no evidence of EFAD after 1 month of lipid limitation.…”
Section: Discussionmentioning
confidence: 98%
“…In this case, we prioritized the potential to salvage the patient's native liver by reversing IFALD and avoiding the need for liver replacement over the development of EFAD with the anticipation that the latter would be short term until the patient receives a transplant and resumes the ability for oral feeding. A recent limited report from Lam et al 8 noted that at an average lipid dose of 0.69 g/kg/d of fat in a cohort of 9 children on PN, there was no evidence of EFAD after 1 month of lipid limitation.…”
Section: Discussionmentioning
confidence: 98%
“…All patients who developed EFAD had a rapid reversal of the condition, when the IVFE dose was increased to 1 g/kg/day three times/week [44]. A more recent study by Lam et al [51] demonstrated that IFER at doses greater than or equal to 1 g/kg/day did not lead to EFAD. In a recent pilot study, the association between IFER and poor neurodevelopmental outcomes was evaluated.…”
Section: Essential Fatty Acid Deficiencymentioning
confidence: 96%
“…In previous studies investigating EFA status in IF patients, the EFAD risk has been reported to be low regardless of lipid source when lipids are administered at the rate of at least 1 g/kg/day. 8,9,11,12 Nevertheless, when enteral feeds increase and the amount of PN decreases, patients may develop deficiencies in multiple micronutrients, including fat-soluble vitamins. These deficiencies are commonly found in children with long-term PN or intestinal insufficiency.…”
Section: Introductionmentioning
confidence: 99%